Implementation of a Standardized Shared Decision-making Bundle to Improve Communication Practices in the Neurocritical Care Unit. Issue 1 (13th February 2023) - Waseem, Hena; Keegan, Joshua; Farrell, Kelly; Hwang, David Y.; Oliver, Brant; Olm-Shipman, Casey; Pepin, Renee; Mecchella, John
Abstract : Background and Objective: Shared decision-making (SDM) aligns patient preferences with health care team treatment goals. This quality improvement initiative implemented a standardized SDM bundle within a neurocritical care unit (NCCU), where unique demands make existing, provider-driven SDM practices challenging. Methods: An interprofessional team defined key issues, identified barriers, and created change ideas to drive implementation of an SDM bundle using the Institute for Healthcare Improvement Model for Improvement framework incorporating Plan-Do-Study-Act cycles. The SDM bundle included (1) a health care team huddle pre-SDM and post-SDM conversation; (2) a social worker–driven SDM conversation with the patient family, including core standardized communication elements to ensure consistency and quality; and (3) an SDM documentation tool within the electronic medical record to ensure the SDM conversation was accessible to all health care team members. The primary outcome measure was percentage of SDM conversations documented. Results: Documentation of SDM conversations improved by 56%, from 27% to 83% pre/postintervention. Average time to documentation decreased by 4 days, from day 9 preintervention to day 5 postintervention. There was no significant change in NCCU length of stay, nor did palliative care consultation rates increase. Postintervention, SDM team huddle compliance was 94.3%. Discussion: A team-driven, standardized SDM bundle that integrates with health care team workflows enabled SDM conversations to occur earlier and resulted in improved documentation of SDM conversations. Team-driven SDM bundles have the potential to improve communication and promote early alignment with patient family goals, preferences, and values.